The genetics of New World monkey visual pigments - BONCI, Daniela Maria Oliveira (2014)
To have color vision, having at least two cone photopigment types with different spectral sensitivities present in distinct photoreceptors is necessary together with the neural circuitry necessary to extract color information. Visual pigments are highly conserved molecules, but differences can be found among vertebrate groups. Primates have a variety of cone photopigments (i.e., opsins) that are expressed by polymorphic genes. This article examines the diversity of cone photopigments in New World monkeys and their behavioral relevance.